2019
DOI: 10.1136/bmj.l4109
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hospital safety following penalties in the US Hospital Acquired Condition Reduction Program: retrospective cohort study

Abstract: Objective To evaluate the association between hospital penalization in the US Hospital Acquired Condition Reduction Program (HACRP) and subsequent changes in clinical outcomes. Design Regression discontinuity design applied to a retrospective cohort from inpatient Medicare claims. Setting 3238 acute care hospitals in the United States. Participants Medicare fee-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…9 The reason for the disparities is likely multifactorial and associated with a complex mix of health care environmental factors and patient-related clinical and social factors, [31][32][33] including the adverse effects of structural racism, discrimination, and toxic stress among patients disproportionately served by safety-net institutions such as those with low income and/or those who identify as members of racial/ ethnic minority groups. [34][35][36][37] Whatever their cause, these disparities in health care-associated infection rates contribute to the disproportionate representation of safety-net hospitals among penalized institutions 11,13 and may have unintended consequences for the financial stability of the safety net and the quality of health care for the patients served. Although Medicaid expansion under the Affordable Care Act reduced uncompensated care costs for many safety-net hospitals, 38,39 these hospitals continue to have low operating margins and often rely on nonclinical sources of revenue 40 or state and federal funds, particularly DSH payments, 41 to offset financial losses associated with remaining uncompensated care and Medicaid reimbursement that is below actual costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The reason for the disparities is likely multifactorial and associated with a complex mix of health care environmental factors and patient-related clinical and social factors, [31][32][33] including the adverse effects of structural racism, discrimination, and toxic stress among patients disproportionately served by safety-net institutions such as those with low income and/or those who identify as members of racial/ ethnic minority groups. [34][35][36][37] Whatever their cause, these disparities in health care-associated infection rates contribute to the disproportionate representation of safety-net hospitals among penalized institutions 11,13 and may have unintended consequences for the financial stability of the safety net and the quality of health care for the patients served. Although Medicaid expansion under the Affordable Care Act reduced uncompensated care costs for many safety-net hospitals, 38,39 these hospitals continue to have low operating margins and often rely on nonclinical sources of revenue 40 or state and federal funds, particularly DSH payments, 41 to offset financial losses associated with remaining uncompensated care and Medicaid reimbursement that is below actual costs.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Safety-net hospitals that care for a higher proportion of patients with low socioeconomic status also tend to demonstrate worse performance, even after accounting for case mix. 9 As a result, safety-net institutions are more likely than non-safety-net facilities to incur financial penalties, [9][10][11][12][13] which may have potential implications for the patients served. 3,[14][15][16] In the case of health care-associated infections, the disproportionate assessment of financial penalties for safety-net institutions could be a factor in worsening financial hardships and subsequently disparities affecting these hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals in the US are penalized financially under the Hospital Readmissions Reduction Program for above-expected readmission rates and under the Hospital-Acquired Condition Reduction Program for above-expected rates of select adverse events. 10,11 Although hospital harm is a known contributor to readmissions, other modifiable factors may be equally or more important. Comprehensive, high-quality transitional care has successfully prevented readmissions by improving patient self-management and continuity of care, while reducing adverse drug events after discharge.…”
Section: Measuring the Cost Of Adverse Events In Hospitalmentioning
confidence: 99%
“…1). While early evaluations of HACRP reported cumulative reductions in hospital-acquired conditions [1,2], more recent studies [3][4][5][6][7] have not found a clear association between receipt of the HACRP penalty and hospital quality of care. For example, recent evidence suggests that HACRP penalized hospitals had more accreditations for quality, offered a larger number of advanced services, were major teaching institutions, and had better performance on other process and outcome measures [7].…”
Section: Introductionmentioning
confidence: 99%